Grid services programming and application enablement - Ferreira, Luis (IBM redbooks., 2004)
The goal of this IBM Redbooks publication is to familiarize the user with the concepts of the OGSA (Open Grid Services Architecture), OGSI (Open Grid Services Infrastructure), Globus Toolkit V3.0, presenting concrete programmatic examples, and also introducing the enhanced features of the IBM Grid Toolbox. We illustrate the various steps needed to develop a grid service application. Existing applications can be wrappered and made available as grid services or applications can be developed from scratch to take advantage of the grid service concepts and provide the benefits made possible by that grid service.